SOSIALISASI PERTANIAN BERKELANJUTAN BAGI MAHASISWA BARU STIPER-FB DI DESA NGINAMANU - Wuli, Rofinus Neto (Merwinspy Publisher, 2023)
This community service activity was conducted to welcome new students of the Sekolah Tinggi Pertanian Flores Bajawa (STIPER-FB) through a socialization and outreach approach themed on sustainable agriculture. Held in Nginamanu Village, the activity engaged 68 participants consisting of new students, lecturers, and local community leaders. The main objective was to foster critical awareness among the younger generation regarding the challenges of farmer regeneration and to introduce the role of technology and innovation in the modern agricultural sector. The method employed was interactive counseling, including material presentations, open discussions, and reflective sessions on the social realities faced by local farmers. Key findings revealed that while most participants showed interest in agricultural issues, they lacked sufficient knowledge about precision farming strategies, e-commerce, and sustainable agriculture concepts. The outreach proved to be an effective medium for encouraging a paradigm shift among youth, who have long perceived farming as an unpromising profession. In conclusion, the activity highlights the strategic role of vocational education institutions such as STIPER-FB in shaping a highly competent agricultural human resource base, while also addressing the challenges of national agricultural development through the early engagement of the millennial generation.